SiC catalytic composite material as well as preparation method and application thereof

By loading CuO/ZnO/CeO2/NiO catalysts onto SiCnws@SiC composite materials and employing in-situ reduction with polyols, the adverse effects of copper-based catalyst growth on ceramic surfaces during loading were resolved, thereby improving catalytic activity and hydrogen production efficiency. In particular, the synergistic effect of the pyroelectricity of 3C-SiC nanowires at high temperatures enhanced catalytic activity and conductivity.

CN120790194APending Publication Date: 2025-10-17HUNAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510774415.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

In the prior art, the step-by-step preparation process of copper-based catalysts on ceramic surfaces has adverse effects on growth, and the Cu0/+ active sites require pre-reduction treatment, which may lead to abnormal catalyst growth and reduced activity.

Method used

By using SiCnws@SiC composite material, CuO/ZnO/CeO2/NiO catalysts are loaded onto the pore walls and surface of a porous SiC matrix, and the in-situ reduction method of polyols is used to maintain the cuprous ions and trivalent cerium ions of the catalyst, thereby improving the catalytic activity.

Benefits of technology

It improves the catalytic activity and hydrogen production effect of the catalyst, and enhances the performance of CuO/ZnO/CeO2/NiO catalyst, especially at high temperature through the synergistic effect of the pyroelectricity of 3C-SiC nanowires, which enhances catalytic activity and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120790194A_ABST
    Figure CN120790194A_ABST
Patent Text Reader

Abstract

The invention provides a SiC catalytic composite material. The SiC catalytic composite material comprises a porous SiC matrix, a 3C-SiC nanowire doped with Ni is loaded on the hole wall of the porous SiC substrate; cuO / ZnO / CeO2 / NiO catalysts are loaded on the surfaces of the pore walls of the porous SiC substrate and the surfaces of the 3C-SiC nanowires. The invention also provides a preparation method of the SiC catalytic composite material and application of the SiC catalytic composite material in the field of catalytic reforming hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of catalysts, in particular to a SiCnws@SiC composite material taking silicon carbide as a matrix and loading copper-based catalysts on silicon carbide nanowires, and a preparation method and application thereof. BACKGROUND

[0002] As an important functional material, SiC has been widely used in various industrial fields, including high-temperature kiln furniture, heat exchangers, sliding bearings, armored bulletproofs, and nuclear fuel cladding materials. The mechanical strength of silicon carbide is higher than that of alumina, its thermal conductivity is nearly four times that of alumina ceramic, and the thermal expansion coefficient of SiC ceramic is lower and the chemical stability is better. Among them, the SiC porous ceramic prepared from SiC powder also has a unique three-dimensional micrometer pore structure, and has the characteristics of low density and high porosity. Therefore, SiC porous ceramic is not only applied to gas filtration, energy storage devices and ceramic membranes, but also considered as an excellent catalyst carrier, and has broad application prospects in the field of thermal catalysis.

[0003] Generally, copper in the prepared copper-based catalyst is usually in an oxidized state (Cu 2+ ), and only Cu 0 / + is the active site, so the catalyst often needs to be pre-reduced by hydrogen before use, which may cause abnormal growth of the catalyst and reduce the catalytic activity. Hydrothermal method is a common method for synthesizing catalysts. By creating a high-temperature and high-pressure environment, catalysts with different compositions and structures can be prepared, and have been used to load copper-based catalysts on ceramic surfaces. However, in the current research on preparing and loading copper-based catalysts on ceramic surfaces by hydrothermal method, step-by-step preparation is basically adopted, which has an adverse effect on the growth, loading and activity of the catalyst. SUMMARY

[0004] The first object of the present application is to provide a SiCnws@SiC composite material.

[0005] The second object of the present application is to provide a preparation method of the SiCnws@SiC composite material.

[0006] The third object of the present application is to provide an application of the SiCnws@SiC composite material.

[0007] The present application is realized by the following technical solutions: A SiC catalytic composite material, comprising a porous SiC matrix; The pore wall of the porous SiC matrix is loaded with 3C-SiC nanowires doped with Ni; The pore wall surface of the porous SiC substrate and the surface of the 3C-SiC nanowire are both loaded with CuO / ZnO / CeO2 / NiO catalyst.

[0008] The porosity of the porous SiC substrate is 40-50%; The pore size of the porous SiC substrate is 19-24 microns.

[0009] The preparation method of the SiC catalytic composite material comprises the following steps: After mixing the soluble carbon source and the silicate, adding organic nickel compound, adding ethanol to hydrolyze the silicate, dissolving the soluble carbon source with water, adjusting the pH to 4-5, a silicon carbide nanowire precursor is obtained; Vacuum impregnating the porous SiC substrate in the silicon carbide nanowire precursor, drying, and heat treating at 1550℃, a porous SiC substrate loaded with 3C-SiC nanowires is obtained; Mixing CuO / ZnO / CeO2 / NiO catalyst powder, polyol and PVA aqueous solution to obtain catalyst slurry; Vacuum impregnating the porous SiC substrate loaded with 3C-SiC nanowires with the catalyst slurry, drying, and heat treating at 220℃ in a protective atmosphere, and the SiC catalytic composite material is obtained.

[0010] The soluble carbon source comprises glucose; The silicate comprises tetraethyl orthosilicate; The organic nickel compound comprises nickel sulfamate; The pH adjusting agent used for adjusting the pH is citric acid.

[0011] The mass ratio of the soluble carbon source and the silicate is 1:1; The amount of the organic nickel compound added is 10% of the total mass of the soluble carbon source and the silicate.

[0012] The concentration of the PVA aqueous solution is 5wt%; The mass ratio of the CuO / ZnO / CeO2 / NiO catalyst powder, glycerol and PVA aqueous solution is 1:1:2; The drying temperature is 90℃; The protective atmosphere comprises argon.

[0013] The preparation method of the porous SiC substrate comprises the following steps: Mixing the first SiC powder with a particle size of 50-100 microns and the second SiC powder with a particle size of 5-10 microns, adding 10wt% of PVA and 10wt% of PMMA, molding, drying and sintering, and the porous SiC substrate is obtained.

[0014] The mass ratio of the first SiC powder and the second SiC powder is 3:1. The pressure of the mold forming is 10 MPa. The sintering temperature is 2400 DEG C.

[0015] The SiC catalytic composite is applied to catalytic reforming hydrogen production.

[0016] The hydrogen production temperature is 340-360 DEG C.

[0017] Compared with the prior art, the application has the following beneficial effects: The CuO / ZnO / CeO2 / NiO catalyst is loaded on the surface of the 3C-SiC nanowire doped with Ni in the SiC catalytic composite provided by the application.

[0018] The preparation method of the SiC catalytic composite provided by the application adopts the in-situ reduction method of polyhydric alcohol to reduce the catalyst.

[0019] The SiC catalytic composite provided by the application can improve the hydrogen production effect and increase the content of hydrogen in the final gas when the SiC catalytic composite is used for reforming hydrogen production. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 The preparation process schematic diagram of SiCnws@SiC is shown; Figure 2 The preparation process schematic diagram of the catalyst and the catalyst coating is shown; Figure 3 The catalyst part characterization results prepared by the embodiment are shown, wherein Figure 3 (a) is the XRD spectrum of the catalyst prepared by the embodiment, Figure 3 (b) is the Raman spectrum of the catalyst prepared by the embodiment; Figure 4 The XPS spectrum of the catalyst prepared by the embodiment is shown, wherein, Figure 4 (a) is Cu 2p, Figure 4(b) is Ce 3d, Figure 4 (c) is Zn 2p, Figure 4 (d) is Ni 2p; Figure 5 The thermogravimetric curve of the catalyst of the SiC catalytic composite prepared in the example is shown; Figure 6 The sample picture of the SiC catalytic composite prepared in the example is shown; wherein, Figure 6 (a-d) are pictures of unloaded catalyst, 1-time impregnation, 2-time impregnation, and 3-time impregnation, respectively; Figure 7 The changes of the catalyst coating before and after ultrasonic vibration under different impregnation coating times are shown; Figure 8 The micro-morphology diagram of the SiC catalytic composite prepared in the example is shown, wherein, Figure 8 (a) is the micro-morphology diagram of the outer surface of the SiC catalytic composite added with 0 wt% PMMA, wherein, (8b) is the micro-morphology diagram of the outer surface of the SiC catalytic composite added with 10 wt% PMMA, Figure 8 (c) is the micro-morphology diagram of the outer surface of the SiC catalytic composite added with 20 wt% PMMA, Figure 8 (d) is the micro-morphology diagram of the outer surface of the SiC porous ceramic directly loaded with the catalyst; Figure 8 (a1) is the micro-morphology diagram of the inner surface of the SiC catalytic composite added with 0 wt% PMMA, wherein, (8b1) is the micro-morphology diagram of the inner surface of the SiC catalytic composite added with 10 wt% PMMA, Figure 8 (c1) is the micro-morphology diagram of the inner surface of the SiC catalytic composite added with 20 wt% PMMA, Figure 8 (d1) is the micro-morphology diagram of the inner surface of the SiC porous ceramic directly loaded with the catalyst; Figure 9 The SEM picture and EDS spectrum analysis picture of the outer surface of the M1 sample are shown, wherein Figure 9 (a) is the SEM picture, Figure 9 (b) is the EDS spectrum analysis picture of Cu, Figure 9 (c) is the EDS spectrum analysis picture of Zn, Figure 9 (d) is the EDS spectrum analysis picture of Ce, Figure 9 (e) is the EDS spectrum analysis picture of Ni, Figure 9 (f) is the EDS spectrum analysis picture of O; Figure 10 The EDS spectrum analysis of the surface of the M1 sample is shown, and the results are as follows Figure 9As shown, in addition to the C, Si elements of the porous ceramic carrier, the elements of the agglomerate are determined to be Cu, Zn, Ce, Ni, O, further confirming the catalyst composition, which is consistent with the results of XDR, etc.

[0021] Figure 10 SEM photos and EDS spectrum analysis pictures of the inner surface of the M1 sample are shown, in which Figure 10 (a) is an SEM photo, Figure 10 (b) is an EDS spectrum analysis picture of Cu, Figure 10 (c) is an EDS spectrum analysis picture of Zn, Figure 10 (d) is an EDS spectrum analysis picture of Ce, Figure 10 (e) is an EDS spectrum analysis picture of Ni, Figure 10 (f) is an EDS spectrum analysis picture of O. Figure 11 The inner surface catalyst weight ratio of the SiC catalytic composite material prepared in the example under different porosities is shown; Figure 12 The hydrogen production performance of the catalyst obtained at different temperatures of the SiC catalytic composite material prepared in the example is shown; Figure 13 The selectivity of the product in the reaction process of the silicon carbide nanowire of the SiC catalytic composite material prepared in the example is shown. Figure 14 The selectivity of the product in the reaction process of the SiC catalytic composite material prepared in the example under different PMMA addition amounts is shown. DETAILED DESCRIPTION

[0022] Embodiment Silicon carbide (the first SiC powder with a particle size of 50-100 microns and the second SiC powder with a particle size of 5-10 microns) with a coarse and fine powder mass ratio of 3:1, 10 wt% of PVA, and 0, 10%, and 20% of PMMA were weighed and mixed in a mortar, then pressed into a φ30 mm × 3 mm test block under 10 MPa for 30 seconds, and dried at 100 ℃ for 24 hours. Finally, the dried sample was placed in a tube furnace in an argon environment, sintered at 2400 ℃ for 2 hours to prepare a silicon carbide porous ceramic.

[0023] Silicon carbide precursor solution was formed by using glucose as a carbon source, tetraethyl orthosilicate as a silicon source, nickel sulfamate as a catalyst, citric acid as a crosslinking agent, adding an appropriate amount of deionized water to form a saturated solution, and anhydrous ethanol to promote the hydrolysis of tetraethyl orthosilicate. The silicon carbide porous ceramic was immersed in the precursor solution for 30 min in a vacuum environment, and after 3 times of immersion-drying, it was placed in a tube furnace with appropriate heating rate and holding time to obtain a SiC composite material. The experimental flow chart is as follows Figure 1.

[0024] The main experimental steps are as follows: Raw material mixing process Glucose and tetraethyl orthosilicate are mixed according to a mass ratio of 1:1, 10% of the total mass of the carbon source and the silicon source is added as nickel sulfamate as a catalyst, 1:1 of the mass ratio of anhydrous ethanol and tetraethyl orthosilicate is added to promote the hydrolysis of tetraethyl orthosilicate, and a proper amount of deionized water is added until the glucose is dissolved. The solution is placed in a heat collecting constant temperature heating magnetic stirrer for stirring, then citric acid is added to adjust the pH value of the solution to 4-5, and the stirring is continued until the stratification disappears, and a sol is formed.

[0025] Heat treatment process The silicon carbide porous ceramic is vacuumed in the precursor solution for 30 min, and the impregnation-drying is repeated for 3 times. The sample is placed in a high-temperature tube furnace, and the temperature is raised to 1550℃ at a heating rate of 5 ℃ / min, and then the furnace is cooled after being kept for 4.5 hours.

[0026] Preparation and loading of CuO / ZnO / CeO2 / NiO catalyst Preparation of CuO / ZnO / CeO2 / NiO catalyst Copper sulfate, zinc acetate, cerium chloride and nickel sulfate are dissolved in deionized water according to a molar ratio of 1:1:1:1, and heated to 60℃. Then under vigorous stirring, 0.5 M aqueous sodium carbonate solution is added dropwise to the salt solution until the pH value of the resulting solution is equal to 8, at which time the four metal ions Cu 2+ , Zn 2+ , Ce 3+ , Ni 2+ combine with OH - to form a precipitate; The resulting precipitate is aged at room temperature for 12 h, and the precipitate is washed several times with deionized water to remove residual Na + . Then the precipitate is dried at 90℃ for 12 h, and calcined at 400℃ for 2 h to convert the precipitated hydroxide to metal oxide, obtaining CuO / ZnO / CeO2 / NiO catalyst.

[0027] Loading of CuO / ZnO / CeO2 / NiO catalyst The CuO / ZnO / CeO2 / NiO catalyst powder, glycerol and 5wt% PVA aqueous solution are mixed according to a mass ratio of 1:1:2 and placed in a ball mill jar, and the mixture is ball milled at a rotation speed of 200 rpm for 2 h to obtain a catalyst slurry, and ultrasonic vibration is performed for 30 min to eliminate the air bubbles generated in the ball milling process; The SiC composite material was immersed in the slurry for 30 min, then slowly pulled out at a constant speed, the excess slurry on the surface of the composite material was removed, and then the composite material loaded with the catalyst slurry was dried at 90 ℃ for 12 h. The above immersion coating process was repeated 3 times; The dried composite material was kept at 220 ℃ for 2 h in argon to obtain an in-situ reduced catalyst coating.

[0028] The phase analysis of the catalyst prepared by the coprecipitation method in the example is as follows Figure 3 . Figure 3 (a) is the XRD pattern of the catalyst, and the diffraction peaks of the catalyst all show the characteristics of low peak intensity and broadening, which are relatively strong CeO2(PDF NO. 34-0394) and ZnO (PDF NO. 36-1451), and weak CuO (PDF NO. 44-0706) and NiO (PDF NO. 44-1159). The Raman spectrum of the prepared catalyst is shown in Figure 3 (b), and obvious peaks of ZnO at 456 cm -1 , CuO at 603 cm -1 and NiO at 1092 cm -1 can be observed. Due to the very close Raman peaks of other metal oxides, the peaks belonging to CeO2 cannot be observed obviously. The peak at 1580 cm -1 belongs to ordered carbon (G bond) and is derived from the residual during washing the precipitate in the preparation process.

[0029] Figure 4 is the XPS spectrum of the catalyst prepared in the example. Copper in the prepared copper-based catalyst usually exists in the form of Cu 2+ , and Cu 2+ does not have catalytic activity, so copper-based catalysts need to be pre-reduced by hydrogen before use. Since copper exists in two valence states of Cu 0 and Cu + after pre-reduction, the discussion about the active sites of the copper-based catalyst is based on these two valence states. Cu + can promote the effective adsorption and activation of carbon monoxide and hydrogen, and carbon dioxide can oxidize Cu 0 to Cu + , so that the concentration of Cu+ is fixed at a certain level. The activity of the catalyst is related to the formation of Cu+ / ZnO with oxygen vacancies. After reduction of the catalyst, the content of Cu + increases sharply, and the catalytic activity also increases, which proves that Cu + is the active site.

[0030] Figure 4In a Cu 2p orbit is divided into characteristic peaks (931.8 eV, 951.6 eV) belonging to Cu 0 / + and characteristic peaks (932.9 eV, 952.8 eV) belonging to Cu 2+ , while the satellite peaks belong to Cu 2+ Cerium oxide (CeO2) is a unique oxide with a fluorite cubic phase structure, in which cerium usually has two valence states of Ce 4+ and Ce 3+ . Specifically, part of Ce 4+ releases lattice oxygen to form Ce 3+ and surface oxygen (Ce 4+ → Ce 3+ + OS), in which the surface oxygen is adsorbed on the surface of CeO2 crystal grains, and oxygen vacancies (VO) are formed in the CeO2 lattice. This feature makes CeO2 widely used in the fields of petrochemical industry and automobile exhaust purification, and also makes it one of the best catalyst additives after ZnO. Figure 4 In (b), the characteristic peaks of Ce 3+ are located at 884.4 eV and 902.5 eV, while the characteristic peaks of Ce4+ are located at 881.5 eV, 888.1 eV, 897.6 eV, 900.1 eV, 906.7 eV and 915.9 eV. Figure 4 In (c), the Zn 2p peaks of all catalysts are sharp and symmetrical, indicating that zinc exists in only one form in each sample. Since the binding energy of Zn-O bond is higher than that of Zn-Zn bond, it can be inferred that zinc exists in the form of Zn 2+ , which is consistent with the results of XRD and Raman spectroscopy. ZnO not only inhibits the sintering of CuO particles, but also promotes the adsorption and dissociation of methanol and water, but when ZnO is reduced to elemental Zn, the above effects will be lost. Figure 4 In (d), the Ni 2p orbit belongs to the characteristic peak of Ni2p3 / 2 (856.7 eV), the satellite peak of Ni 2p3 / 2 (862.4 eV) and the satellite peak of Ni 2p1 / 2 (883.8 eV, 888.3 eV).

[0031] The present application further performs thermogravimetric analysis on the catalyst prepared in the example, and the results are shown in Figure 5 . The curve starts to decline from 100℃, at which time the surface adsorbed water in the catalyst starts to evaporate, and as the temperature continues to rise, a small amount of residual precursor decomposes.

[0032] The porosity (P) of the SiC porous ceramics was measured by Archimedes drainage method. First, the SiC porous ceramics was placed in boiling water for one hour, the wet weight (m3) and the suspended weight (m2) of the sample were measured; second, the sample was placed in an oven to dry the moisture and the dry weight (m1) was measured; finally, the porosity of the sample was calculated by the formula The pore size of the sample was tested by using a microfiltration membrane pore size analyzer, and the results are shown in Table 1.

[0033] Table 1 Figure 6 The sample pictures of the SiC catalytic composite material prepared in the example are shown in (a-d), which are respectively unloaded catalyst, impregnated once, impregnated twice, and impregnated three times. As can be seen from the figure, the catalyst coating is bright red due to the presence of elemental copper. With the increase of the impregnation times, the catalyst coverage on the surface of the sample increases, and cracks appear on the surface, which leads to the easy falling off of the catalyst coating.

[0034] Figure 7 The changes of the catalyst coating before and after ultrasonic vibration under different impregnation times are shown in the figure. The mass change of the catalyst coating after ultrasonic vibration can be used to explore the bonding strength of the catalyst coating. It can be seen that the mass of the catalyst coating gradually increases from 0.40 g after the first impregnation to 0.60 g after the third impregnation. Since the pore size of the SiC porous ceramics is small, the mass of the catalyst after the third impregnation only increases by 0.06 g compared with the second impregnation, which indicates that the catalyst coating has been difficult to enter the pores of the porous ceramics and only stays on the surface. The catalyst coating after the third impregnation has cracks, which leads to a low bonding strength of the coating, so the impregnation times are not increased. The weight loss rate of the catalyst coating after the third impregnation is less than 10% in the same ultrasonic time, which indicates that the catalyst coating in this study has good bonding strength, which is beneficial to improve the structural stability of the catalyst coating in the continuous reaction process.

[0035] Figure 8 The micro-morphology of the SiC catalytic composite material prepared in the example is shown in the figure. (a), (b), (c) are respectively without PMMA (M1), adding 10% PMMA (M2), and adding 20% PMMA (M3), and SiCnws are grown in situ. (d) is pure SiC porous ceramics directly loaded with catalyst (M4). As can be seen from Figure 8 (a), (b), (c), (d), agglomerates can be observed on the outer surface of the four samples, part of the micropores are covered, and there are some cracks. Since the outer surface is impregnated with catalyst, no obvious SiC nanowires can be observed on the outer surface. The EDS spectrum analysis of the surface of the M1 sample is shown in the figure. Figure 9As shown, in addition to the C, Si elements of the porous ceramic carrier, the elements of the agglomerates were determined to be Cu, Zn, Ce, Ni, O, further confirming the catalyst composition, consistent with the results of XDR, etc. Figure 8 (a1), (b1), (c1), (d1) are four sample inner surface micro-morphology graphs, and it is observed that the inner surfaces of samples M1, M2 and M3 all have silicon carbide nanowires. From M1 to M3, as the PMMA addition amount increases, the pore size of the silicon carbide porous ceramic also increases, and more growth space is provided for the silicon carbide nanowires. EDS spectrum analysis was performed on the inner surface of sample M1, as shown in Figure 10 The prepared catalyst composition was detected on the entire inner surface, indicating that the catalyst entered the silicon carbide porous ceramic carrier well, and all elements had good dispersity. Similarly, EDS spectrum analysis was performed on the remaining three samples, and the results were consistent with M1. Through EDS mapping analysis of the inner surfaces of M1, M2 and M3 samples, the element composition of the catalyst was determined, Figure 11 The weight percentage of the catalyst on the inner surface of the sample under different porosities is shown in Figure 11 As shown, as the porosity increases, more catalyst enters the sample interior.

[0036] Reaction temperature is also an important condition affecting the hydrogen production performance of the catalyst. Under the reaction conditions of mixing deionized water and methanol in a molar ratio of 1:1.05, a reaction material feeding speed of 0.112 mol / h, and studying the effect of reaction temperature on the methanol conversion rate, it is shown from Figure 12 As the temperature increases, the content of H2 in the produced gas increases, the content of CO2 decreases, and the content of CO also increases to a certain extent. This is because the methanol steam reforming is an endothermic reaction, and the increase in temperature promotes the forward progress of the methanol steam reforming reaction, resulting in an increase in the content of H2. When the temperature is 280℃, the H2 selectivity is only 48.18 %, when the temperature rises to 360℃, the H2 selectivity increases to 90.18 %, and when the temperature continues to rise to 400℃, the H2 selectivity increases to 90.35 %, and the change in H2 selectivity is small. Because lower temperature is more economical and energy-saving, therefore, the optimal reaction temperature is 360℃.

[0037] In order to explore the effect of SiCnws on the catalytic activity, under the reaction conditions of mixing deionized water and methanol in a molar ratio of 1:1.05, a reaction temperature of 340 ℃~360 ℃, and a reaction material feeding speed of 0.112 mol / h, the performance of the sample in methanol reforming hydrogen production was evaluated. The results are as shown in Figure 13As shown, hydrogen is the main product. In the sample containing SiCnws, the H2 content in the product gas is increased to 90.38%, the content of the by-product CO2 is reduced, but the content of CO in the sample is increased. The increased production of H2 in the sample containing SiCnws can be attributed to the pyroelectricity of SiCnws, which belongs to 3C-SiC, and the cubic structure of 3C-SiC has the characteristics of electric polarization or surface charge when the temperature changes, so SiCnws can act as a catalyst in cooperation with the metal catalyst, thereby increasing the content of H2, on the other hand, it also promotes the reverse water gas shift reaction (CO2+H2→CO+H2O) and methanol decomposition reaction (CH3OH→CO+H2) to increase the content of CO.

[0038] Under the conditions of reactant feed rate of 0.112 mol / h, deionized water / methanol molar ratio of 1:1.05, and reaction temperature of 340 ℃~360 ℃ fluctuation, the influence of the porosity of SiC porous ceramics on the catalytic activity was studied. Figure 14 The gas selectivity under different porosity conditions is shown, when PMMA is not added, the H2 selectivity is 90.18 %, when PMMA is added by 10 %, the H2 selectivity is increased to 90.16 %, and when the amount of PMMA continues to increase to 20 %, the H2 selectivity is reduced to 86.92 %. Combined with the microstructure of the sample, it can be seen that when the amount of PMMA is 10 %, the growth condition of silicon carbide nanowires is better than that of the sample without adding PMMA and the catalyst loading content is also increased. Under long-term use, the sample with 10 % PMMA will have better hydrogen production performance.

[0039] The present application uses SiC porous ceramics loaded with 3C-SiC nanowires as a catalyst carrier, loads catalyst in SiC porous ceramics by in-situ reduction of glycerol, and characterizes the properties of the catalyst. At the same time, the effects of SiCnws, reaction temperature and porosity of porous ceramics on the catalytic performance in the hydrogen production reaction of methanol steam reforming are tested, and the following conclusions are obtained: After adding PMMA, the porosity and pore size of the sample are increased to a certain extent, further providing more space for SiCnws and catalyst.

[0040] Through hydrogen production platform test by methanol steam reforming, in 280 DEG C ~ 400 DEG C temperature, with the temperature increasing gradually, H2 selectivity gradually increases, at 360 DEG C and 400 DEG C, the selectivity of H2 has no obvious change, in the loaded catalyst sample, under the temperature shock, the sample of in-situ growth SiCnws shows good H2 selectivity, the pyroelectricity of SiCnws and catalyst improves the selectivity of H2, under the condition of different porosity of porous ceramics, when the PMMA addition amount is 10 %, the number of SiCnws in the sample is greater than that of the sample without adding PMMA. The optimal reaction temperature of SiC catalytic composite material provided by the application for hydrogen production by methanol steam reforming is in the range of 340 DEG C ~ 360 DEG C.

Claims

1. A SiC catalytic composite material, characterized in that: including a porous SiC matrix; The pore walls of the porous SiC matrix are loaded with 3C-SiC nanowires doped with Ni; The pore wall surface of the porous SiC matrix and the surface of the 3C-SiC nanowire are both loaded with CuO / ZnO / CeO2 / NiO catalysts.

2. The SiC catalytic composite material according to claim 1, characterized in that: The porosity of the porous SiC substrate is 40-50%; The pore size of the porous SiC substrate is 19-24 microns.

3. The method for preparing the SiC catalytic composite material according to claim 1, wherein: The steps include: After mixing a soluble carbon source with silicate, an organic nickel compound is added, ethanol is added to hydrolyze the silicate, water is added to dissolve the soluble carbon source, and the pH is adjusted to 4 to 5 to obtain a silicon carbide nanowire precursor; The porous SiC substrate was vacuum impregnated in a silicon carbide nanowire precursor, dried, and heat-treated at 1550°C to obtain a porous SiC substrate loaded with 3C-SiC nanowires; The CuO / ZnO / CeO2 / NiO catalyst powder, polyol and PVA aqueous solution are mixed to obtain a catalyst slurry; The porous SiC substrate loaded with 3C-SiC nanowires is vacuum impregnated with catalyst slurry, dried, and heat-treated at 220° C. in a protective atmosphere to obtain the product.

4. The method for preparing the SiC catalytic composite material according to claim 3, wherein: The soluble carbon source includes glucose; The silicate comprises ethyl orthosilicate; The organic nickel compound includes nickel sulfamate; The pH regulator used was citric acid.

5. The method for preparing the SiC catalytic composite material according to claim 3, wherein: The mass ratio of soluble carbon source to silicate is 1:1; The amount of the organic nickel compound added is 10% of the total mass of the soluble carbon source and the silicate.

6. The method for preparing the SiC catalytic composite material according to claim 3, wherein: The concentration of the PVA aqueous solution is 5wt%; The mass ratio of the CuO / ZnO / CeO2 / NiO catalyst powder, glycerol and PVA aqueous solution is 1:1:2; The drying temperature is 90°C; The protective atmosphere includes argon.

7. The method for preparing the SiC catalytic composite material according to claim 3, wherein: The preparation method of the porous SiC substrate comprises the following steps: After mixing a first SiC powder with a particle size of 50-100 microns and a second SiC powder with a particle size of 5-10 microns, 10 wt% of PVA and 10 wt% of PMMA are added, molded, dried and then sintered to obtain the product.

8. The method for preparing the SiC catalytic composite material according to claim 7, wherein: The mass ratio of the first SiC powder to the second SiC powder is 3:1; The compression molding pressure is 10 MPa; The sintering temperature is 2400°C.

9. The use of the SiC catalytic composite material according to claim 1, characterized in that: Applied to catalytic reforming to produce hydrogen.

10. The use of the SiC catalytic composite material according to claim 9, characterized in that: The temperature of the hydrogen production is 340-360°C.